Literature Study: The Effectiveness of Inquiry Learning Models with Visual Media in the Material of Healthy, Nutritious and Balanced Diets on Students’ Cognitive Learning Outcomes in Junior High Schools - Anggraeni, Nevy; Rahman, Andi; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to know the effectiveness of inquiry learning models with visual media on PJOK subject. One of the materials in PJOK subject is on healthy, nutritious and balanced diets. The method that is used in this research is Qualitative Research which is a literature study, in which the data are collected from various related literatures. The data collecting technique in this research uses literature study technique. The stages of the research are conducted from collecting the articles, article reduction, discussion and conclusion. The data sources of the research are articles of national and international journals. The obtained data are analyzed and centralized efficiently and basically further will be described. Based on some researches that have been analyzed, it can be concluded that the inquiry learning models can improve the student learning development on PJOK subject on the material of healthy, nutritious and balanced diets. The result of literature study shows that the inquiry learning models can support the learning activeness, improve the scientific thinking of the students, and also can improve the learning outcomes.